Hemicraniectomy for large middle cerebral artery territory infarction: outcome in 19 patients. Issue 6 (1st June 2003) - Pranesh, M B; Dinesh Nayak, S; Mathew, V; Prakash, B; Natarajan, M; Rajmohan, V; Murali, R; Pehlaj, A
Abstract : Background: Large space-occupying middle cerebral artery infarction accounts for 10–15% of all supratentorial infarctions and carries a mortality of 50% to 80%. Hemicraniectomy may be useful when optimal medical management has failed. Methods: Between June 1997 and June 2000, 19 patients who fulfilled the clinical and imaging criteria for large middle cerebral artery infarction underwent hemicraniectomy because of impending herniation despite best medical therapy. The National Institute of Health Stroke Scale (NIHSS) assessed neurological status on admission and at one week after surgery. At 3 month follow up, The Barthel Index (BI) and Rankin Scale (RS) were used to assess the functional outcome among survivors. Results: There were 15 males and 4 females with a mean age of 46.5 years (range 27–76 years). Ten patients (53%) had dominant hemisphere stroke. The mean interval between stroke onset and surgery was 60.3 hours (range 20–103 hours). The mean NIHSS score before surgery was 20.5 (range 17–26) and 10.5 (range 6–22) after surgery. One patient (5.2%) died due to post-operative meningitis. At follow up, mean BI was 56.4 (range 25–90) and RS revealed severe handicap in 4 patients (21%). Patients under 50 years of age had a significantly better outcome with mean BI of 60.7 as compared to only 41.3 (p=<0.048) in older patients. Speech function, especially comprehension improved in all patients with dominant hemisphere infarction. Conclusion: These findings add to previous studies suggesting hemicraniectomy may be a useful procedure in patients with large middle cerebral artery territory infarction. The functional outcome is good in younger patients. A randomised controlled trial is required to substantiate these findings.